2.5x(x+2)+4.5x=1.5(x-4)

Simple and best practice solution for 2.5x(x+2)+4.5x=1.5(x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2.5x(x+2)+4.5x=1.5(x-4) equation:


Simplifying
2.5x(x + 2) + 4.5x = 1.5(x + -4)

Reorder the terms:
2.5x(2 + x) + 4.5x = 1.5(x + -4)
(2 * 2.5x + x * 2.5x) + 4.5x = 1.5(x + -4)
(5x + 2.5x2) + 4.5x = 1.5(x + -4)

Reorder the terms:
5x + 4.5x + 2.5x2 = 1.5(x + -4)

Combine like terms: 5x + 4.5x = 9.5x
9.5x + 2.5x2 = 1.5(x + -4)

Reorder the terms:
9.5x + 2.5x2 = 1.5(-4 + x)
9.5x + 2.5x2 = (-4 * 1.5 + x * 1.5)
9.5x + 2.5x2 = (-6 + 1.5x)

Solving
9.5x + 2.5x2 = -6 + 1.5x

Solving for variable 'x'.

Reorder the terms:
6 + 9.5x + -1.5x + 2.5x2 = -6 + 1.5x + 6 + -1.5x

Combine like terms: 9.5x + -1.5x = 8x
6 + 8x + 2.5x2 = -6 + 1.5x + 6 + -1.5x

Reorder the terms:
6 + 8x + 2.5x2 = -6 + 6 + 1.5x + -1.5x

Combine like terms: -6 + 6 = 0
6 + 8x + 2.5x2 = 0 + 1.5x + -1.5x
6 + 8x + 2.5x2 = 1.5x + -1.5x

Combine like terms: 1.5x + -1.5x = 0.0
6 + 8x + 2.5x2 = 0.0

Begin completing the square.  Divide all terms by
2.5 the coefficient of the squared term: 

Divide each side by '2.5'.
2.4 + 3.2x + x2 = 0

Move the constant term to the right:

Add '-2.4' to each side of the equation.
2.4 + 3.2x + -2.4 + x2 = 0 + -2.4

Reorder the terms:
2.4 + -2.4 + 3.2x + x2 = 0 + -2.4

Combine like terms: 2.4 + -2.4 = 0.0
0.0 + 3.2x + x2 = 0 + -2.4
3.2x + x2 = 0 + -2.4

Combine like terms: 0 + -2.4 = -2.4
3.2x + x2 = -2.4

The x term is 3.2x.  Take half its coefficient (1.6).
Square it (2.56) and add it to both sides.

Add '2.56' to each side of the equation.
3.2x + 2.56 + x2 = -2.4 + 2.56

Reorder the terms:
2.56 + 3.2x + x2 = -2.4 + 2.56

Combine like terms: -2.4 + 2.56 = 0.16
2.56 + 3.2x + x2 = 0.16

Factor a perfect square on the left side:
(x + 1.6)(x + 1.6) = 0.16

Calculate the square root of the right side: 0.4

Break this problem into two subproblems by setting 
(x + 1.6) equal to 0.4 and -0.4.

Subproblem 1

x + 1.6 = 0.4 Simplifying x + 1.6 = 0.4 Reorder the terms: 1.6 + x = 0.4 Solving 1.6 + x = 0.4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.6' to each side of the equation. 1.6 + -1.6 + x = 0.4 + -1.6 Combine like terms: 1.6 + -1.6 = 0.0 0.0 + x = 0.4 + -1.6 x = 0.4 + -1.6 Combine like terms: 0.4 + -1.6 = -1.2 x = -1.2 Simplifying x = -1.2

Subproblem 2

x + 1.6 = -0.4 Simplifying x + 1.6 = -0.4 Reorder the terms: 1.6 + x = -0.4 Solving 1.6 + x = -0.4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.6' to each side of the equation. 1.6 + -1.6 + x = -0.4 + -1.6 Combine like terms: 1.6 + -1.6 = 0.0 0.0 + x = -0.4 + -1.6 x = -0.4 + -1.6 Combine like terms: -0.4 + -1.6 = -2 x = -2 Simplifying x = -2

Solution

The solution to the problem is based on the solutions from the subproblems. x = {-1.2, -2}

See similar equations:

| 3x+x-3=25 | | 0.2(n-5)=0.3n+6-4+0.1n | | -.55(x+2)=4.4 | | -8=(3-d)4 | | -2x+4y=-40 | | 1600=p(1+0.06) | | 5m-15-20m+5= | | (3x+6)(2x-12)(x+8)=0 | | -4y-2x=-8 | | -1.5x+y=320 | | 6f-13=24f-11 | | 6f-13=24f | | 1.4x+2y=800 | | 5*x-9+2*x+3=90 | | -4(x-2)+6x-15-x(4-3)=14-3(x+2)+7x-4 | | 0=-16 | | 380=2(w)(w+20) | | 5*4-9+2*4+3= | | 11+10=-8 | | 9+.75x=.875x-10 | | 5(4-3c)-6(2c+1)= | | 3t-2=t+10 | | 5(3)+x=21 | | 20x+345=51x+651 | | b=v*4-9 | | 6x-y-11=0 | | 2d=4d-425 | | 38-6x+7=10x+12+9x+5x-15x-24+15x-6 | | 2x+25=12x | | 27-2p=-(6p+2)+5 | | h=1+9.5t+(-4.9t^2) | | 3.6a+7.5=29.1 |

Equations solver categories